Changes in vertical ground reaction forces with fatigue during the serve in tennis - Girard, O.; Millet, G. P.; Micallef, J. P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Recent biomechanical analyses of the tennis serve have focused on lower extremity kinematics, ground reaction forces (GRF) or EMG activity of selected leg muscles, underlying the importance of a forceful lower limb drive to produce efficient strokes. A decrease in isometric maximal voluntary strength capacity of both knee extensors and plantar flexors has been reported after prolonged tennis playing. However, strength losses with fatigue - as measured previously from isolated leg muscle contractions - do not necessarily reflect changes in lower limb involvement during dynamic/functional movements such as tennis strokes. Therefore, it is still unknown if fatigue alters the lower limb drive during the serve. The purpose of this study was to examine the impact of prolonged tennis playing on vertical GRF during the serve. Methods Nine competitive tennis players randomly executed 10 flat (first, FS), 5 slice (first, SS) and 5 twist (second, TS) serves before and after a 2 h 30 min tennis match. All serve trials were completed from the deuce service court at match pace. Vertical maximal GRF (Fzmax) and post-impact ball velocity were determined for each trial by means of force platform (Captels, France) and radar (Stalker, USA), respectively. Results/Discussion Ball velocity did not change from pre- to post-exercise (FS: 158.7±11.5 vs. 154.7±11.5 km.h-1, -2.5%, P=0.099; SS: 138.2±21.6 vs. 136.5±20.8 km.h-1, -1.1%, P>0.05; TS: 126.3±20.2 vs. 124.9±15.3 km.h-1, -0.4%, P>0.05). In the literature, contrasting effects of fatigue on tennis serve efficiency have been reported depending on service type, nature of fatiguing protocol or subjects` characteristics. In the fatigued state, Fzmax was unchanged (P>0.05) in FS and SS (1.78±0.30 vs. 1.72±0.29 and 1.60±0.22 vs. 1.65±0.22 BW; -2.9 and +3.8%; before and after the tennis match, respectively). In line with these findings, no significant changes in explosive strength - as measured from squat and countermovement jumps - were observed after a tennis match protocol of the same duration. Unexpectedly, our results also displayed an increased Fzmax (1.62±0.25 vs. 1.75±0.23 BW; +8.2%; P<0.001; before and after the tennis match, respectively) in TS under fatigue. Since the ball velocity was unchanged, this stronger lower limb involvement during TS under fatigue might indicate that the contribution of other body segments participating to the kinetic chain (trunk, upper limbs) is modified. This is further supported by the absence of significant correlation between changes in Fzmax and ball velocity (0.03 < r < 0.62; P>0.05) from pre- to post-exercise. Conclusion After a prolonged tennis match, ball velocity remains unchanged while the effects of fatigue on the lower limb drive are different according to the service type. This indicates a modification in inter-segments coordination that requires further kinematic and kinetic analyses coupling.